Occupational Health of Staff Nurses Working in Private Hospitals during the Early Post-Pandemic Period of COVID-19 - Blancaflor, Edmar E; Cariaga, Ma. Ericka Jhanina L; Coloma, Jeselle Angelene B; Pangcoga, Hainah S; Corpuz, Alfrey J; Santos, Jonalyn P (South East Asia Nursing Research, 2024)
Background: COVID-19 pandemic has significantly impacted healthcare professionals, causing issues like anxiety, hopelessness, and difficulty sleeping. Occupational health encompasses nurses' physical, mental, emotional, and social well-being, and has been significantly affected due to the pandemic on nurses' work and the resulting changes in their occupational health.Objective: This study assessed the level of occupational health among staff nurses' in private hospitals during the early post-pandemic period in the northern part of the Philippines.Methods: This study utilized a mixed-method design implemented in private hospitals in Tuguegarao City, Cagayan, to gather data on occupational health and wellness on a sample size of 100 nurses during the early post-pandemic period. The researchers used a purposive sampling technique and a questionnaire with adopted and modified questions as well as a self-made question. Frequency and percentage was used to describe the profile and mean to present the level of occupational health. Analysis of Variance was used to determine difference in level of the occupational health of nurses according to their profile. Thematic analysis was used to analyze qualitative data.Results and Discussion: Results show that staff nurses have good level of occupational health during the early post-pandemic period. Moreover, qualitative data revealed that nurses experienced many health issues during the peak of the pandemic, and that they experienced an improvement of their overall occupational health during the early post-pandemic period. The staff nurses experienced reduced anxiety, performed better self-care and observed stricter adherence to infection prevention and control protocols which greatly affected their occupational health.Conclusion: It can be concluded therefore that the occupational health of nurses during the early post-pandemic period of COVID-19 pandemic has improved compared to during the pandemic. Their experiences during the pandemic led to less anxiety, improved self-care and better compliance with IPC protocols.